Pengaruh Lingkungan Sekolah dan Aktivitas Keagamaan Terhadap Perilaku Religius Siswa di SMA IT Granada Samarinda - Sonia, Sonia (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
This study aims to investigate the influence of the school environment and religious activities on students’ religious behavior at SMA IT Granada Samarinda. The research is motivated by the imperative to cultivate students’ religious character as a fundamental component of the national education objectives. Employing a quantitative method with an associative approach, data were collected through structured questionnaires administered to 52 respondents, comprising 11th-grade students at SMA IT Granada Samarinda. The data analysis involved descriptive statistics, classical assumption testing, and multiple linear regression analysis using SPSS software. The findings reveal that the school environment exerts a positive and statistically significant influence on students’ religious behavior. Likewise, religious activities demonstrate a positive and significant impact on students’ religious behavior. Furthermore, both independent variables, when examined simultaneously, contribute significantly to the enhancement of students’ religious conduct. These results underscore the pivotal role of a supportive school environment and the consistent implementation of structured religious programs in shaping students’ religious character.